Metabolic Effects of Long-Term Reduction in Free Fatty Acids With Acipimox in Obesity: A Randomized Trial - Makimura, Hideo (J Clin Endocrinol Metab, 2016)
CONTEXT: Increased circulating free fatty acids (FFAs) have been proposed to contribute to insulin resistance in obesity. Short-term studies have investigated the effects of acipimox, an inhibitor of hormone-sensitive lipase, on glucose homeostasis, but longer-term studies have not been performed. OBJECTIVE: To test the hypothesis that long-term treatment with acipimox would reduce FFA and improve insulin sensitivity among nondiabetic, insulin-resistant, obese subjects. DESIGN, SETTING, PATIENTS, AND INTERVENTION: At an academic medical center, 39 obese men and women were randomized to acipimox 250 mg thrice-daily vs identical placebo for 6 months. MAIN OUTCOME MEASURES: Plasma lipids, insulin sensitivity, adiponectin, and mitochondrial function via assessment of the rate of post-exercise phosphocreatine recovery on (31)P-magnetic resonance spectroscopy as well as muscle mitochondrial density and relevant muscle gene expression. RESULTS: Fasting glucose decreased significantly in acipimox-treated individuals (effect size, −6 mg/dL; P = .02), in parallel with trends for reduced fasting insulin (effect size, −6.8 μU/mL; P = .07) and HOMA-IR (effect size, −1.96; P = .06), and significantly increased adiponectin (effect size, +668 ng/mL; P = .02). Acipimox did not affect insulin-stimulated glucose uptake, as assessed by euglycemic, hyperinsulinemic clamp. Effects on muscle mitochondrial function and density and on relevant gene expression were not seen. CONCLUSION: These data shed light on the long-term effects of FFA reduction on insulin sensitivity, other metabolic parameters, and muscle mitochondrial function in obesity. Reduced FFA achieved by acipimox improved fasting measures of glucose homeostasis, lipids, and adiponectin but had no effect on mitochondrial function, mitochondrial density, or muscle insulin sensitivity.